A comparative analysis of the efficacy of a combined topical therapy in patients suffering from mild to moderate papulopustular acne - YU. S. Kondratiyeva; T. N. Shepileva; O. A. Kokina; YE. A. Subbotin (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The goal of this study was to compare the efficacy and safety of Azelic (15% gel of azelaic acid), 1% Clindamycin gel and 0.1% Adapalene gel as a complex therapy in patients suffering from mild to moderate acne. Materials and methods. An open-label comparative study involving 40 patients suffering from mild to moderate papulopustular acne. The study was based on the medical history, a questionnaire form, physical examination results, assessment of morphological and functional skin parameters and dynamics of the life quality index (DLQI). Key findings and conclusions. Positive dynamics of the skin process was observed by the end of Week 6 of the treatment depending on the combination treatment type. The administration of Azelic gel resulted in an increased moisture level of the skin and reduced sebometry indices, skin relief intensity and pigmentation level.